Remote Sensing of Mid/Upper Atmosphere using ELF/VLF Waves (Global Journal of Science Frontier Research, 2018)
Radio signals from lightning discharges such as be used in the study of radio wave propagations and ultimately the ionospheric/ conditions. In the present paper, we have whistlers (very low-frequency waves) as a diagnostic tool for remote atmosphere. These ELF/VLF waves installed at our low latitude ground station, Lucknow geomagnetic longitude = 154.5 0 E, Mc Ilwain parameter, L = 1.10), India. Tweeks have used to estimate the nighttime D-region electron density whistlers have provided information about magnetospheric medium dispersion, electron density, total electron radio signal generated during lightning discharges. During our analysis, we existence duration of tweeks to be in the range of estimated from 22.51 -132.46 cmreflection height varied from 80 -94.4 km.
Keywords: lightning discharges; tweeks; whistlers; ionosphere; magnetosphere; electron density; hybrid mode of propagation; dispersion